Evaluation of Optic Nerve Head Biomechanical Properties in Pseudoexfoliation Glaucoma with Real-time Elastography - Unal, Ozlem; Caglayan, Mehtap; Kosekahya, Pinar; Yulek, Fatma; Taslipinar, Guzin (Current Medical Imaging, 2019)
Purpose: To investigate the biomechanical properties of the optic nerve head in patients with Pseudoexfoliation (PEX) glaucoma using Real-time Elastography (RTE) and to compare these results with those of Primary Open Angle Glaucoma (POAG) patients and healthy subjects. Methods: Twenty eyes of 20 PEX glaucoma patients (PEX group), 20 eyes of 20 POAG patients (POAG group), and 20 eyes of 20 healthy subjects (control group) were enrolled in this prospective study. The strain Ratios of Orbital Fat to Optic Nerve head (ROFON) and lateral rectus muscle to optic nerve head (RLRON) were determined. Comparisons were performed using Chi-square, Kruskal Wallis, Mann-Whitney U, and One-way ANOVA tests. Results: The strain ratios of orbital fat to optic nerve head were 2.34, 6.85 and 1.76 in PEX glaucoma, POAG, and control groups, respectively (p<0.001). The strain ratios of the lateral rectus muscle to the optic nerve head were 0.51, 0.82, and 0.55 in PEX glaucoma, POAG, and control groups, respectively (p=0.256). Conclusion: The strain ratios of orbital fat to optic nerve head were different in PEX glaucoma patients than in POAG and control groups. RTE can provide biomechanical assessment of the optic nerve head in a non-invasive, quick, easily accessible, and user-friendly manner.
Keywords: optic nerve head biomechanics